Linking cognitive reserve to neuropsychological outcomes and resting-state frequency bands in healthy aging - Perez, Vanesa; Hidalgo, Vanesa; Salvador, Alicia (Frontiers in Aging Neuroscience, 2025)
IntroductionAs the proportion of older people has surged in the past 100 years, healthy aging has emerged as a crucial topic in neuroscience research. This study aimed to investigate the spectral power of EEG frequency bands during resting-state in older people with high and low cognitive reserve (CR).MethodsTo do so, 74 healthy older people (55–74 years old) were recruited and divided into two groups based on their level of CR: high CR (n = 41; 21 men and 20 women) and low CR (n = 33; 15 men and 18 women). Both groups participated in a cognitive assessment and 3 min of EEG recording under resting-state conditions with eyes open (EO) and eyes closed (EC). EEG power was analyzed across four frequency bands: delta (0.1– < 4 Hz), theta (4– < 8 Hz), alpha1 (8–10 Hz), alpha2 (10–12), and beta (14–30 Hz), focusing on five cortical regions of interest.ResultsNeuropsychological tests did not reveal significant differences between the two groups on most of the cognitive measures. However, the EEG analysis showed that individuals with high CR exhibited lower spectral power in the theta and delta frequency bands across different brain regions, compared to those with low CR.DiscussionThese findings suggest that individuals with high CR tend to function more efficiently, relying on fewer neural resources to sustain cognitive performance. In contrast, those with low CR may engage compensatory neural mechanisms, as indicated by increased spectral power while resting, conceivably reflecting the brain’s effort to preserve cognitive function.